Sensory-perceptual regulation thinking process - Vitaliy Shmarhun (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
Тhe article deals with the sensory-perceptual regulation as an entry-level imagery perception and thinking. There is some connection between the indicators of sensory and perception and the indicators psychometric intelligence among adolescent children who had different level of IQ. The connection based on empirical data is shown in the article.